Effects of lenalidomide and dexamethasone treatment duration on survival in patients with relapsed or refractory multiple myeloma treated with lenalidomide and dexamethasone - San-Miguel, J.F.; Dimopoulos, M.A.; Stadtmauer, E.A.; Rajkumar, S.V.; Siegel, D.; Bravo, M.-L.; Olesnyckyj, M.; Knight, R.D.; Zeldis, J.B.; Harousseau, J.-L.; Weber, D.M. (Clinical Lymphoma, Myeloma and Leukemia, 2011)
Background: In two randomized phase III trials (MM-009 and MM-010), lenalidomide plus dexamethasone significantly prolonged time to progression and overall survival (OS) in patients with relapsed/refractory multiple myeloma compared with dexamethasone alone. In both trials the treatment was continued until disease progression or unacceptable toxicity. We conducted a subanalysis to determine if continuing therapy after achieving ≥ partial response (PR) improved survival. Patients and Methods: Data were collected on 212 patients who were treated with lenalidomide plus dexamethasone and achieved ≥ PR. Kaplan-Meier survival estimates were compared between patients on continued treatment versus patients discontinuing therapy because of adverse events, withdrawal of consent, or other reasons. Time-dependent multivariate regression analyses were used to determine the benefit of continuing treatment with lenalidomide. Results: A total of 174 patients received continued treatment until disease progression or death, and 38 patients discontinued therapy without progression. There was a trend toward longer median OS in patients who continued therapy (50.9 months vs. 35.0 months; P = .0594). When controlling for the number of previous antimyeloma therapies, β2-microglobulin levels, and Durie-Salmon stage (which adversely affected survival in these patients), continued lenalidomide treatment (HR, 0.137; 95% CI, 0.045-0.417; P = .0005) or each additional cycle of lenalidomide (HR, 0.921; 95% CI, 0.886-0.957; P < .0001) were both associated with longer survival. Conclusion: Continued lenalidomide treatment until disease progression after achievement of ≥ PR is associated with a significant survival advantage when controlling for patient characteristics. These findings should be confirmed in a prospectively designed trial. © 2011 Elsevier Inc. All rights reserved.
Keywords: Granulocyte colony-stimulating factor; MM-009; MM-010; Neutropenia; Partial response; Thrombocytopenia